Refleksi terhadap Model Kepemimpinan Qur’ani - Siti Aimah; Abdi Fauji Hadiono (IAI Darussalam, 2019)
Leadership in life is always closely related. This is because no human is able to live individually in this world, meaning they need social relations for their survival, especially humans. It is this social relationship that then makes individuals lead individuals or a group of other individuals. Therefore discussing leadership is indeed needed to make the concept of leadership that is good and feasible to be applied in human life at the level of social relations, moreover in the viewpoint of socio-religious relations, especially religious Islam. Starting from this view, the Qur'ani leadership whose concept is based on the Qur'an (as a guideline for life) is important to study. So this paper describes the definition of leaders and leadership from experts, the task of leaders, characteristics of leaders, skills that must be possessed, and become leaders with the characteristics (criteria) of the Qur'ani leadership. Thus his hopes will provide a clear picture of the Qur'ani leadership which is currently recognized as ammunition in achieving effective and contributory leadership for the future.